ANALISIS PENGARUH PENGGUNAAN PEMBAYARAN DIGITAL QRIS TERHADAP KENAIKAN OMSET PENJUALAN PADA UMKM - Pratiwi, Larasati Azzahra; Ningsih, Nanda Arfia; Amaliah, Faqihah; Tiara Sri Intan (STIE-PMCI, 2024)
Digital transformation has changed the transaction system from cash to cashless transactions. However, the current use of QRIS is not quite familiar among MSMEs and there are still many MSMEs that have not implemented QRIS digital payments as a record of sales turnover. The purpose of writing this article is to discuss QRIS digital payments to increase MSME sales turnover. The research data uses multiple linear analysis which aims to test how much influence QRIS has on sales turnover. The nine independent variables are QRIS user literacy, QRIS implementation, QRIS usage, QRIS user capability, QRIS user convenience, QRIS user service prices, QRIS user satisfaction, QRIS user efficiency improvement, QRIS user strategy and increased sales turnover as dependent variables. The value of the R2 coefficient of determination of 0.159315 or 15.93% shows that the nine variables used together can be significant sales turnover as dependent variables.